ANALISIS GAYA KEPEMIMPINAN DEMOKRATIS DALAM MENINGKATKAN KINERJA KARYAWAN DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) KARYA USAHA MANDIRI (KUM) BOGOR CABANG JATIBARANG - Nugraha, Gilang Pratama; Trihantana, Rully; Mursyidah, Azizah (SAHID BANKING JOURNAL, 2023)
This study aims to analyze the leadership style of KSPPS KUM Bogor, Jatibarang Branch and to analyze the democratic leadership style of KSPPS KUM Bogor, Jatibarang Branch in improving employee performance. The subjects of this study were employees at KSPPS KUM Bogor Jatibarang Brebes Branch. This research uses a qualitative approach with a qualitative descriptive research type. The results of this study are: (1) Discipline, (2) Dedication and (3) Understanding of Tasks. The leadership style carried out by the deputy head of the KSPPS KUM Bogor Branch Jatibarang is a democratic leadership style, which has been carried out by the head branches by always implementing discipline in work, motivating, accepting criticism and suggestions from employees, having high dedication and also in making decisions based on the results of deliberations in realizing the main goals of the company. The conclusions of this study are: (1) The democratic leadership style at KSPPS KUM Bogor Branch Jatibarang has influenced the performance of employees at work seen from the leadership prioritizing deliberation in making decisions and also providing jobdesk motivation or rewards to employees, this has an effect on performance employees (2) democratic leadership style deputy head of KSPPS KUM Bogor Branch Jatibarang has implemented a democratic leadership style in improving the performance of its employees.